Review on Text Detection and Extraction for Catching Identities of Objects in Road Video Scenes - Choudhary, Namrata; Jain, Kirti (International Journal of Computer Sciences and Engineering, 2025)
In the current scenario there are different types of research has been performed in the field of text detection and extraction from images. Different types of processes used different types of application of the text extraction from the images. With the help of the Text Extraction process we can easily find important data from images. There are various types of Image processing techniques have been evolved for Text Extraction from the image scene and videos. Every process has different types of factors like Precision, Speed, Complexity and Time required, etc. but each process gives different result in each field. Some process has advantage and disadvantage related to these factors, so we can say single process is inadequate for the complete process of text detection and extraction. For the preferable performance, we present the combine form of different processes. This paper contains combination of two different processes for text detection and extraction from video surveillance system just like processing of images from image scenes.